Tell a different story: some reflections on the 11th Kilbrandon Lecture and its relevance to residential child care - Frank Cottrell Boyce; Irene Stevens (Scottish Journal of Residential Child Care)
Stories are a part of every culture, helping people to understand their history, their hopes and their fears. However, it is only in recent times that the importance of storytelling in residential childcare has begun to be explored.